Spatial distribution of the immigrant population in the catalonian municipalities: identity, exposition, concentration and centrality - Martori Cañas, Joan Carles; Hoberg, Karen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Given the important growth in the number of immigrants in Spain it is interesting to study their distribution throughout the urban area. There are different indices of long standing tradition in statistics which are at our disposal andallow us to quantify the segregation of minority population groups. Through the application of these tools on the Catalan case, its use in the analysis of residential segregation in a town and in uncovering the patterns which underlie it are shown.The results point out that there does not exist a clear relationship between foreign population percentages and their segregation,and that segregation differs depending on the observed group. A new perspective on segregation can be obtained through the use of indices designed with the help of elements from spatial statistics. The combination of all these measures represents a useful procedure for the analysis of the distribution of immigrants in urban spaces and it use fulness can be extended to different areas such as sociology, economics, urbanismor housing policies.
Keywords: Residential segregation; Immigration; Segregation indices; Spatial statistics